Biogeographical crossroad across the Pillars of Hercules: Evolutionary history of Psammodromus lizards in space and time. (24th September 2017) - Mendes, Joana; Harris, D. James; Carranza, Salvador; Salvi, Daniele
Abstract: Aim: To infer the biogeographical and evolutionary history of the Western Mediterranean Psammodromus lizards with the aim of assessing the role of vicariance and dispersal on the cladogenetic events within the palaeogeological dynamics of the Strait of Gibraltar. Location: North Africa and Western Europe. Methods: We built a dataset including all six species of Psammodromus using mitochondrial ( 12S, cytb, nd4 ) and nuclear ( acm4, mc1r, pomc ) gene fragments. Species tree and concatenation methods were used to infer phylogenetic relationships and divergence times. Phylogenies were used for biogeographical inference using S‐DIVA, DEC and BBM. Results: Psammodromus probably originated in Iberia, with P. algirus diverging early. The ancestor of the African P. blanci and P. microdactylus dispersed to Africa through the Betic‐Rif massif, c . 10 Ma. The cladogenetic events within Africa and Iberia were probably due to vicariance mediated by habitat and climatic changes at the end of the Miocene ( P. blanci and P. microdactylus ) and during the Pliocene ( P. occidentalis, P. hispanicus and P. edwardsianus ). Psammodromus algirus shows three lineages, two in Iberia and one in Africa, the latter originated following a transmarine dispersal during the Middle Pleistocene (1.5 Ma). Main conclusions: Over‐sea dispersal has played a major role in intercontinental exchange and divergence in Psammodromus, with two dispersal events towards Africa that occurred 10 and 1.5 Ma resulting in the African lineages. This study, combined with previous literature, provides compelling evidence that major biotic exchanges took place across the Strait of Gibraltar well before or long after the land connection during the Messinian Salinity Crisis (MSC, 5.9–5.33 Ma). These findings suggest caution in the application of the relatively short event of Atlantic flooding at the end of the MSC as cause for divergence in molecular clock calibrations, which is a popular approach in literature.